Avaliação imuno-histoquímica dos marcadores de angiogênese VEGF e angiopoietina-2 em carcinoma hepatocelular e lesões precursoras em explantes de pacientes cirróticos - Teixeira, André Costa (2016)
Hepatocellular carcinoma (HCC) is a global health problem and is associated with chronic liver disease, especially in the cirrhotic phase. This tumor can be preceded by precursor lesions, namely low and high grade dysplastic nodules, and regenerative nodules, typical of cirrhosis. The current study evaluated the immunohistochemical expression of VEGF and angiopoietin-2 in HCC and precursor lesions is a single institution series of liver explants between 2013-2015 using tissue microarray methods. Immunohistochemical variables were correlated with angiogenesis and prognostic parameters. 107 nodules from 67 patients were studied, including 26 HCC and 5 dysplastic nodules. There was no significant epidemiologic difference between HCC, dysplastic nodules and regenerative nodule groups. Angiopoietin-2 was significantly more expressed in HCC nodules when compared with regenerative lesions (p < 0,0001*). VEGF and Ang-2 expression correlated with each other (p=0,006) and with number of unpaired arteries within nodules (p=0,03 – VEGF) and with the percentage of CD34 positive sinusoids (p < 0,0001 – VEGF and p< 0,007 – Ang-2). There was no significant correlation between any of the immunohistochemical parameters with clinical staging, number of gross lesions and histologic grade in cases of HCC. Angiopoietin-2 had a sensitivity of 54% and 96,25% of specificity for HCC diagnosis, and VEGF had a sensitivity of 69,23% and specificity of 31,25%. Our study shows that Ang-2 may be a good marker for HCC diagnosis when compared to others that are routinely used for this purpose. VEGF is not a good marker due to its lack of specificity, although other studies showed that it may be associated with prognostic parameters. Finally, our data reinforce the importance of angiogenesis evalutation in the development of HCC and its potential applicability as a diagnostic tool.